Evaluation of the Participants’ Participation in Family Planning Program during Covid-19 Pandemic in Malang City - Arfida Boedirochminarni; Zaenal Arifin (Universitas Muhammadiyah Malang, 2022)
COVID-19 has been declared a world pandemic by WHO (WHO, 2020). And it has also been stated that the Head of the National Disaster Management Agency through Decree number 9 A of 2020 has been extended through Decree number 13 A of 2020 as the Status of Certain Emergency Disasters due to Corona Virus Disease Outbreaks in Indonesia. Then by looking at the developing situation and conditions, it was updated with Presidential Decree no. 12 of 2020 concerning the Determination of Non-Natural Disasters for the spread of COVID-19 as a National Disaster (Ministry of Health of the Republic of Indonesia, 2020). Based on the results of the evaluation of male and female family planning participants based on the type of contraceptive device, all experienced a decline during the covid 19 period. This was because during the covid period many family planning service officers at the Yandu Post were not as active as usual, especially with the PPKM, all family planning activity programs were stopped. . However, when viewed from the level of participation of contraceptive users, there are 7 types. For male contraceptives it is 28.57%, while the participation rate for women is 71.43%.